How do coaches experience psychological momentum? A qualitative study of female elite handball teams - Moesch, K.; Apitzsch, E. (The Sport Psychologist, 2012)
Psychological Momentum (PM) is commonly referred to in competitive sports, but still has to be considered elusive from a scientific perspective. This study explores coaches` perception of triggers, strategies and characteristics of PM in female elite handball teams. Semi-structured interviews with nine coaches were evaluated using a qualitative content analysis. The results revealed that positive and negative PM were characterized by factors regarding behavior, cognition, confidence, emotions, and the team. Triggers for positive PM were categorized into confidence, players` individual factors, team factors, and team-opponent-factors, whereas triggers for negative PM related to coach factors, confidence, external factors, players` individual factors, and team factors. Moreover, strategies emerged that are considered beneficial for controlling PM. The results are discussed with emphasis on behavioral aspects, confidence, emotions, team factors, and application. Foundations based on this study and recent research lead to the assumption that PM is probably best portrayed in a circular approach.